KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Dewi Rahayu; Ellen Rusliati (JRAK, 2019)
The aim of this study to determine the effect of institutional ownership, managerial ownership, firm size, to dividend policy simultaneously and partially. The population of this study are manufacturing companies in the consumer goods industry sector listed in Indonesia Stock Exchange of 2008-2017, the sample amounted 6 companies. The method used in this study are descriptive and verificative using panel data regression analysis. The results showed that the simultaneously institutional ownership, managerial ownership and firm size has significant effect on dividend policy with contribution of effect equal to 39.62%. The partially, institutional ownership has a significant positive effect on dividend policy, managerial ownership has a significant negative effect on dividend policy, firm size has a significant positive effect on dividend policy. The effect contribution dominant of independent variables is institutional ownership equal to 29.2%, managerial ownership equal to 10% and firm size equal to 0.4%.